Combined effects of soot load and catalyst activity on the regeneration dynamics of catalytic diesel particulate filters. Issue 5 (20th December 2017) - Di Sarli, Valeria; Di Benedetto, Almerinda
Abstract : The combined effects of soot load and catalyst activity on the regeneration dynamics of a catalytic diesel particulate filter have been investigated through transient CFD‐based simulations of soot combustion in a single‐channel configuration. The soot load was changed by varying the amount of soot accumulated as cake layer, while keeping the amount of soot trapped inside the catalytic wall constant. Substantially uniform soot combustion that allows reasonably fast regeneration of the filter under controlled temperature conditions has been simulated only in the absence of cake and at relatively low catalyst activity. Conversely, in the presence of cake, numerical predictions have shown that, regardless of both soot load and catalyst activity, fast regeneration always occurs by propagation of sharp reaction fronts that result in high temperature rises. These findings highlight the importance of avoiding the cake formation, while properly optimizing the catalyst activity, to conduct a safe and effective regeneration of catalytic filters. © 2017 American Institute of Chemical Engineers AIChE J, 64: 1714–1722, 2018